(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Croatian family legislation went through several reforms in the last twenty years and this paper focuses on the matrimonial property regime after the most recent legislative intervention in 2015. The Family Act 2015 tried to attach more importance to the matrimonial property relations, thus providing for some significant changes and novelties. While there were certainly legitimate aims behind the changes introduced, for example increasing the level of legal certainty in the real estate trading or the protection of the child’s wellbeing in the cases of breaking the family union with respect to its right to habitation, it is doubtful whether those aims are achieved. The relevant provisions of the Family Act 2015 raise some serious concerns and generate certain new problematic points but at the same time leave previously opened issues unresolved. The author analyses the regulation of the matrimonial property regime with the purpose of detecting its advantages and its shortcomings as well as indicating the possibilities for improving the existing situation.